Green supply chain management : reverse logistics - Huang, MengZhen (2014)
With ever increasing consumer awareness and their willingness to return products, leads to the need of taking RL system into deeper considerations. In simpler term, RL is defined as a strategic process that has to be well-planned and managed in order to recapture the value of products as well as to encourage appropriate waste disposals. RL has gained increased attention from the various industries over the recent years, with the aim of achieving cost savings, improving customer service and ultimately raising the bottom-lines of companies. There are few other driving forces to which why there is an increasing trend for the implementation of RL system. The report mainly intends to address the implications of having a RL system and identify the relationship it has with the profitability of companies.